Mahtab roye bom - Torabi, Amir Hosain (Iran : Torabi, Amir Hosain, 2007)
A young man visits a painter and asks him to draw the girl he has seen on the beach. For weeks, the painter tries unsuccessfully to capture the features of the enigmatic girl his customer calls Mahtab (moonlight), until one day the young man's mother knocks on his door and reveals the moonlight girl.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Fiction films